Fuzzy Sets and System - International Fuzzy Systems Association (Amsterdam : Elsevier, 1978)
Access available online from 1995- through ScienceDirect
Published: Elsevier, <2005->
Keywords: Fuzzy sets -- Periodicals; Fuzzy systems -- Periodicals; Fuzzy sets; Fuzzy sets -- Periodicals; Fuzzy systems -- Periodicals